(untitled) (Research, Society and Development, 2022)
Slash-and-burn agriculture is still a predominant production system in tropical forests, however, studies carried out in several parts of the world indicate that production systems are in the process of transition, having diminished or even being extinct. The objective of this article is to understand the changes in the dynamics of the slash and burn system developed by family farmers in the municipality of Altamira, Pará. In the study, 50 families residing in the Assurini Settlement Project, located near the municipality’s headquarters, were interviewed. The data were analyzed with an interdisciplinary approach, approaching qualitative and quantitative aspects. It was found that there was a decrease in annual crops and an expansion of livestock activity. The main drivers of these changes were the decrease in family labor, the lack of access to markets and the environmental legislation that limits the use of primary forest areas to establish new swiddens. Despite these changes, this cultivation system is important for families, as it guarantees production for family consumption and diversification of production. However, greater involvement of social actors and institutions is necessary, in the sense of investing in diversification, and in technologies that make it possible for cultivated areas to be used for a longer period of time, avoiding the deforestation of new areas.